Challenges in end-of-life dementia care. Issue 3 (18th May 2018) - Fetherston, Anne A; Rowley, Grace; Allan, Charlotte L
Abstract : Dementia is a chronic, progressive disease that is now much more widely recognised and treated. Patients with dementia may require palliative care when they reach the end stage of their illness, or they may have mild–moderate cognitive symptoms comorbid with a life-limiting illness. The variety of presentations necessitates a highly individual approach to care planning, and patients should be encouraged to set their own goals and contribute to advanced care planning where possible. Assessment and management of distressing symptoms at the end of life can be greatly helped by a detailed knowledge of the individuals' prior wishes, interdisciplinary communication and recognition of changes in presentation that may result from new symptoms, for example, onset of pain, nutritional deficits and infection. To navigate complexity at the end of life, open communication that involves patients and families in decisions, and is responsive to their needs is vital and can vastly improve subjective experiences. Complex ethical dilemmas may pervade both the illness of dementia and provision of palliative care; we consider how ethical issues (eg, providing care under restraint) influence complex decisions relating to resuscitation, artificial nutrition and treatment refusal in order to optimise quality of life.